Intra- and inter-reader agreement of iRECIST and RECIST 1.1 criteria for the assessment of tumor response in patients receiving checkpoint inhibitor immunotherapy for lung cancer. (November 2021) - Huicochea Castellanos, Sandra; Pagano, Andrew; Plodkowski, Andrew J.; Girshman, Jeffrey; Hellmann, Matthew D.; Rizvi, Hira; Flynn, Jessica; Zheng, Junting; Capanu, Marinela; Halpenny, Darragh F; Ginsberg, Michelle S
Highlights: Substantial agreement among iRECIST readers for treatment response in lung cancer. Treatment response assessment using iRECIST is comparable to RECIST 1.1. RECIST 1.1 underestimates the treatment effects of immunotherapy. Radiologist experience does not affect accuracy of iRECIST assessment. Abstract: Objectives: To investigate the inter- and intra-reader agreement of immune Response Evaluation Criteria in Solid Tumors (iRECIST) and Response Evaluation Criteria in Solid Tumors version 1.1 (RECIST 1.1) in patients with lung cancer treated with immunotherapy. Materials and Methods: This retrospective study included 85 patients with lung cancer treated with PD-1 blockade. Four radiologists evaluated computed topography (CT) scans before and after initiation of immunotherapy using iRECIST and RECIST 1.1. Weighted kappa (k) with equal weights was used to assess the intra-reader agreement between 2 repeated reads on overall response at all time points, best overall response, and the response at the time point of progression, as well as the intra-reader agreement between iRECIST and RECIST. The inter-reader agreement was calculated using Light's kappa. Results: Intra-reader agreement for overall response at all time points, best overall response, and time point of progression was substantial to almost perfect for both iRECIST and RECIST 1.1 (k = 0.651–0.983). Inter-reader agreement was substantial for iRECIST (κ = 0.657–0.742) while RECIST 1.1 was moderate to substantial (κ = 0.587–0.686). The level of inter-reader agreement was not higher on repeat read for iRECIST (κ = 0.677–0.709 and κ = 0.657–0.742 for first and second read, respectively) as well as for RECIST 1.1 (κ = 0.587–0.659 and κ = 0.633–0.686 for first and second read, respectively). Almost perfect agreement was observed between RECIST 1.1 and iRECIST at first (κ = 0.813–0.923) and second read (κ = 0.841–0.912). Conclusion: The inter- and intra-reader agreement of iRECIST is high and similar to RECIST 1.1 in patients with lung cancer treated with immunotherapy.